Analisis Butir Soal Ujian Sekolah Menggunakan Program Iteman (Analysis of School Exam Questions Using the Iteman Program) - Rizka Abri Pradani; Anwar Efendi (Jurusan Tadris Bahasa Indonesia, 2023)
This study aims to analyze the items based on content validity, reliability, level of difficulty, item discrimination, and the operation of the distractor on the junior high school examination questions in Rembang Regency for the 2021/2022 academic year. Data were obtained from the answer sheets of 32 students of SMPN 1 Kaliori using the Iteman program. The results showed that seven items were in the difficult category, 20 were in the moderate category, and 13 were in the easy category. Meanwhile, based on the Differential Power Index (IDB), it can be seen that seven items are in a bad category, 13 items are in the sufficient category, 14 items are in a good category, and 2 items are in the very good category. The rest are in a bad category. The test item writing team can use research findings as evaluations, and teachers can use them to improve the quality of each item tested.Penelitian ini bertujuan menganalisis butir soal berdasarkan validitas isi, reliabilitas, tingkat kesukaran, daya pembeda soal, dan pengoperasian distraktor pada soal Ujian Sekolah SMP di Kabupaten Rembang Tahun Pelajaran 2021/2022. Data diperoleh dari lembar jawaban 32 siswa SMPN 1 Kaliori dengan menggunakan program Iteman. Hasil penelitian menunjukkan bahwa tujuh butir soal berkategori sulit, 20 berkategori sedang, dan 13 berkategori mudah. Adapun berdasarkan Indeks Daya Beda (IDB) dapat diketahui bahwa tujuh butir soal berkategori buruk, 13 butir soal berkategori cukup, 14 butir soal berkategori baik, dan 2 butir soal berkategori sangat baik. Sisanya berkategori tidak baik. Tim penulis soal tes dapat menggunakan temuan penelitian sebagai evaluasi, dan guru dapat menggunakannya untuk meningkatkan kualitas setiap item yang diuji.